Organizational design in the public universities of Peru - Moran Cusi, Saul (2022)
Organizational design is essential in all universities, it defines the elements and characteristics of how it is going to be organized, it has the main function of establishing authority, hierarchy, chain of command, organization charts, among others. Currently, public university entities in Peru play an important role in development. For several years, the university system in Peru with its organizational designs did not facilitate the proper flow of its processes, since it had non-coherent organizational designs. The main objective of this article is to present an organizational design proposal for public universities in Peru, through reviews of the regulatory framework related to organizational designs in university entities. In the conclusions, information is provided to the public servants who participate in university management. It contributes to creating the capacity to build coherent organizational designs, with new and powerful means of coordination, that respond to the complexity of the environment and are capable of aligning with the strategy, adequately managing the parties involved and incorporating new technologies